A brief history of the International Diatom Symposium - Edlund, Mark B.; Andresen, Norman A. (Phytotaxa, 2013)
The International Diatom Symposium began as the "First Symposium on Recent and Fossil Marine Diatoms" in Bremerhaven, Germany in 1970 with 15 diatomists in attendance. The informal group decided to meet on a biennial basis with meetings moving to different venues across Europe. The group grew with each of the early meetings and came to recognize the need to include both marine and freshwater researchers at the symposium. At the fifth meeting of the group, the name was changed to reflect this; the "Fifth Symposium on Recent and Fossil Diatoms" was held in Antwerp, Belgium in 1978. The meeting eventually adopted the name "International Diatom Symposium" at the 1982 seventh meeting in Philadelphia, Pennsylvania, USA. In 1986, at the Ninth International Diatom Symposium in Bristol, UK, the International Society for Diatom Research (ISDR) was formally established and has used the International Diatom Symposium to hold their biennial meetings of the Council and the Society. The IDS continues as a biennial gathering of international diatomists with symposia venues proposed by members, subjected to member vote, and given final council approval. The Society has encouraged meetings beyond European and American venues; notable venues have included the first Asian meeting (Fourteenth International Diatom Symposium, in Tokyo, Japan), the first Australian meeting (Fifteenth International Diatom Symposium, in Perth, Australia), and a symposium held in Russia (Nineteenth International Diatom Symposium in Irkutsk, Russia).